PERLINDUNGAN DATA PRIBADI SEBAGAI INSTRUMEN HUKUM DALAM MENANGGULANGI KEJAHATAN PERBANKAN - Noris Sugiarto; Indra Yuliawan; Arista Candra Irawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digital transformation in the banking sector has enhanced the efficiency of financial services while simultaneously increasing the risk of data-driven banking crimes. Customers’ personal data have become both the object and the primary means of various criminal activities, such as identity theft, phishing, and misuse of financial information. This condition necessitates robust personal data protection as an integral part of the banking legal system. This article aims to analyze the concept of personal data protection in the context of banking crimes, examine the legal framework governing personal data protection in the Indonesian banking sector, and explain the urgency of personal data protection as a legal instrument for preventing banking crimes. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that Law Number 27 of 2022 on Personal Data Protection strengthens the principle of bank secrecy and functions as both a preventive and repressive legal instrument in addressing data-based banking crimes. Personal data protection plays a crucial role not only in safeguarding customers’ rights but also in maintaining public trust and the stability of the national banking system.